Advances in Materials Science for Precision Melanoma Therapy: Nanotechnology-Enhanced Drug Delivery Systems - Sivakumar S. Moni; Jobran M. Moshi; Sabine Matou-Nasri; Shmoukh Alotaibi; Yousef M. Hawsawi; Mohamed Eltaib Elmobark; Ahlam Mohammed S. Hakami; Mohammed A. Jeraiby; Ahmed A. Sulayli; Hassan N. Moafa (Pharmaceutics)
Melanoma, a highly aggressive form of skin cancer, poses a major therapeutic challenge due to its metastatic potential, resistance to conventional therapies, and the complexity of the tumor microenvironment (TME). Materials science and nanotechnology advances have led to using nanocarriers such as liposomes, dendrimers, polymeric nanoparticles, and metallic nanoparticles as transformative solutions for precision melanoma therapy. This review summarizes findings from Web of Science, PubMed, EMBASE, Scopus, and Google Scholar and highlights the role of nanotechnology in overcoming melanoma treatment barriers. Nanoparticles facilitate passive and active targeting through mechanisms such as the enhanced permeability and retention (EPR) effect and functionalization with tumor-specific ligands, thereby improving the accuracy of drug delivery and reducing systemic toxicity. Stimuli-responsive systems and multi-stage targeting further improve therapeutic precision and overcome challenges such as poor tumor penetration and drug resistance. Emerging therapeutic platforms combine diagnostic imaging with therapeutic delivery, paving the way for personalized medicine. However, there are still issues with scalability, biocompatibility, and regulatory compliance. This comprehensive review highlights the potential of integrating nanotechnology with advances in genetics and proteomics, scalable, and patient-specific therapies. These interdisciplinary innovations promise to redefine the treatment of melanoma and provide safer, more effective, and more accessible treatments. Continued research is essential to bridge the gap between evidence-based scientific advances and clinical applications.